High density DNA methylation array with single CpG site resolution - Bibikova, Marina; Barnes, Bret; Tsan, Chan; Ho, Vincent; Klotzle, Brandy; Le, Jennie M.; Delano, David; Zhang, Lu; Schroth, Gary P.; Gunderson, Kevin L.; Fan, Jian-Bing; Shen, Richard (Genomics (San Diego, Calif.), 2011)
We have developed a new generation of genome-wide DNA methylation BeadChip which allows high-throughput methylation profiling of the human genome. The new high density BeadChip can assay over 480K CpG sites and analyze twelve samples in parallel. The innovative content includes coverage of 99% of RefSeq genes with multiple probes per gene, 96% of CpG islands from the UCSC database, CpG island shores and additional content selected from whole-genome bisulfite sequencing data and input from DNA methylation experts. The well-characterized Infinium® Assay is used for analysis of CpG methylation using bisulfite-converted genomic DNA. We applied this technology to analyze DNA methylation in normal and tumor DNA samples and compared results with whole-genome bisulfite sequencing (WGBS) data obtained for the same samples. Highly comparable DNA methylation profiles were generated by the array and sequencing methods (average R2 of 0.95). The ability to determine genome-wide methylation patterns will rapidly advance methylation research. ► New-generation high-throughput DNA methylation platform provides a true genome-wide coverage of over 485K sites. ► Content selected with guidance of a Consortium comprised of 22 methylation experts from 19 institutions worldwide. ► Coverage distributed across gene regions, including promoter, 5' UTR, first exon, gene body and 3' UTR. ► Broad coverage includes CpG islands, regulatory and differentially methylated regions, DHS sites, non-CpG loci and other content. ► Methylation profiles highly correlated with whole-genome bisulfite sequencing data.